Atributos químicos dos solos dos Departamentos de Misiones, Itapúa e Alto Paraná - Paraguai - John, Roberto Willian (2014)
The Precision Agriculture (PA) is considered an important tool for management of modern agriculture and fertilization recommendations supported on this tecnology whose main purpose assist in decision making processes in fertilizer application. The objective of this work was to make a diagnosis of soil fertility in Eastern Region of Paraguay , according to the levels of organic matter, phosphorus, potassium and pH . As a secondary objective , we estimated the need for application of agricultural lime for the studied region. Were classified 11,130 soil samples belonging to the firm "Sustentap Agricultura de Precisão" in 5 classes of Fertility (Very Low, Low, Medium, High and Very High) adapted the regional calibration data used in "Cooperativa Colônias Unidas" (Paraguay). Samples belonging to the study , the main limitations of fertility were found to Organic Matter in the Departments of Misiones with 98.12 % and 74.27 % in Itapúa with the samples in Medium, Low and Very Low classes; Potassium in the Department of Misiones, with 94.85 % of the samples to Low or Very Low ; Phosphorus in the Department of Itapúa with 67.02 % of the samples in Low or Very Low and Alto Paraná with 79.46 % levels focusing on levels Very Low, Low and Medium; pH presented at the Department of Misiones 98.63 % of the samples with levels Low or Very Low and the Department of Alto Parana with a total of 83.71 % of the samples below Medium level . Concerning the application of agricultural lime to increase the pH to optimum levels the need was 1.68, 1.71 and 1.56 Mg ha-1 for the Departments of Misiones, Alto Paraná and Itapúa respectively. It is verified so that the cost of fertilization application to the variable rate is lower than the cost of applying the fertilizer with fixed average rate.